Incidence and Presentation of Molar Pregnancy at Bahawal Victoria Hospital, Bahawalpur - SADIA SHAKIL, SAMINA AKRAM, TASNEEM AKHTAR, NOREEN AKMAL, (Journal of Fatima Jinnah Medical University, 2018)
Background: Gestational Trophoblastic Disease (GTD) forms a group of disorder including hydatidiform mole, invasive mole, choriocarcinoma and placental-site trophoblastic tumor. The objective of this study was to find out the incidence and clinical presentation of GTD at our institution. Patients and Methods: One year retrospective, descriptive study conducted at Gynae Unit-II of Bahawal Victoria Hospital, Bahawalpur, from 1st Januay 2013 to 31st December 2013. Complete blood picture, blood grouping, serum β-hCG level, ultrasonograpghy and chest X-ray were done. The patients presented with various forms of GTD were noted for histopathology, incidence and clinical presentation. Results: A total of 28 cases of GTD out of 4530 gynecological admissions were diagnosed. The incidence of GTD was 6.1 / 1000. Histopathology revealed that 25 (89.3%) had hydatidiform mole. Out of these 25 patients, 19 (76%) were having complete mole. Most patients, 27 (96.4%) were having a risk score of < 7. Majority of the patients (53.6%) were between 20-30 years of age. There were 14 (50.0%) patients who were either Para 0 or Para 1. Majority, 22 (78.6%) patients were diagnosed during the first trimester. Amenorrhea was reported in all the patients while abnormal vaginal bleeding (85.7%) and uterus size enlargement (71.4%) were the commonest mode of presentation. Only one patient (3.5 %) died. Conclusion: The incidence of GTD is 6.1 / 1000 in the study population. Abnormal vaginal bleeding and increased uterus size are the commonest mode of presentation.